Legal Analysis of Unpaid Loss Insurance Claims Against Rental Cars - Muhammad Dhobit Azhary Lubis; Sarah Furqoni (LEGAL BRIEF, 2022)
A loss insurance claim is a form of the insured's right to demand compensation for an insurance object that experiences an event, namely an uncertain event, it can be an accident, damages that have been stated in the policy, even fatally the insurance object is lost. Submitting an insurance claim for the insured must first complete the requirements for filing a loss insurance claim such as the necessary documents, facts that actually occurred at the scene of the case where all of these requirements can be seen in the policy.The purpose of this study is to find out how the form of a loss insurance policy for rental cars is, how to submit a loss insurance claim against rental cars, and how to analyze the law of unpaid loss insurance claims against rental cars. To achieve the research objectives, a juridical research was conducted, namely data analysis that revealed and retrieved the truth obtained from the literature by combining regulations, scientific books that had to do with the "title". Then it is analyzed qualitatively so that it gets a problem solving and a conclusion can be drawn. Based on the research results, It is understood that the loss insurance claim that is not paid for the rental car is due to the dishonesty of the insured against the insurer at the time of entering into the insurance agreement. The insurance agreement made between the insured and the insurer is a loss insurance agreement for a private car, the object of which must be used in accordance with its form as a private car that is not used as a rental car. The basic principle in this insurance agreement is the principle of honesty and goodwill between the insured and the insurer. As is the case with agreements in general, insurance agreements are subject to 4 (four) important principles for the validity of an agreement according to the Civil Code, namely the principle of freedom of contract, the principle of consensualism, the principle of pacta sunt servanda, and the principle of good faith. Due to the intentional element of the insured party to benefit from the insured car by means of rental, therefore, the insurance party cannot compensate for the insured object and the insured party has violated the principle of the agreement which resulted in the agreement being void.